(untitled) (Communications in Computational Physics, 2022)
Graphene nanoribbons are considered as one of the most promising ways to design electron devices where the active area is made of graphene. In fact, graphene nanoribbons present a gap between the valence and the conduction bands as in standard semiconductors such as Si or GaAs, at variance with large area graphene which is gapless, a feature that hampers a good performance of graphene field effect transistors. To use graphene nanoribbons as a semiconductor, an accurate analysis of their electron properties is needed. Here, electron transport in graphene nanoribbons is investigated by solving the semiclassical Boltzmann equation with a discontinuous Galerkin method. All the electron-phonon scattering mechanisms are included. The adopted energy band structure is that devised in [1] while according to [2] the edge effects are described as an additional scattering stemming from the Berry-Mondragon model which is valid in presence of edge disorder. With this approach a spacial 1D transport problem has been solved, even if it remains two dimensional in the wave-vector space. A degradation of charge velocities, and consequently of the mobilities, is found by reducing the nanoribbon width due mainly to the edge scattering.